Muscle structure and gene expression in pectoralis major muscle in response to deep pectoral myopathy induction in fast- and slow-growing commercial broilers - Yalcin, S.; Şahin, Kazım; Tuzcu, M.; Bilgen, G.; Ozkan, S.; Izzetoglu, G. T.; Isik, R. (Taylor & Francis Ltd, 2019)
1. The objective of this study was to determine muscle structure and gene expression in pectoralis major (p. major) muscle of broilers in response to deep pectoral myopathy (DPM) induction.2. A total of 160 chickens from slow- and fast-growing broilers were raised under same conditions. Half of the broilers from each strain were encouraged to wing flap when they reached 2800g body weight. Pectoralis minor (p. minor) muscle of the broilers was inspected for the occurrence of DPM and p. major samples were collected from broilers with or without DPM. The muscle fibre area and number, capillary number and the signalling pathways of vascular development (vascular endothelial growth factor A, VEGFA) and muscle contraction regulation (actin alpha 1, ACTA1; myosin light chain kinase 2, MYLK2 and ATPase Ca+2 transporting gene 1, ATP2A1) were studied in p. major muscle.3. DPM induction increased fibre area of p. major muscle with a greater rate in the slow-growing strain compared with fast-growing line. Although the capillary number was higher in slow-growing compared with fast-growing broilers, in the case of DPM induction, the number of capillaries was similar between strains.4. Expression of VEGFA, MYLK2 and ATP2A1 was greater in slow- than in fast-growing broilers. DPM induction increased expression of ACTA1, VEGFA and ATP2A1 in p. major muscle of broilers from both strains; however, MYLK2 expression was downregulated.5. Changes in capillary density and expression of VEGFA found in the p. major muscle of broilers with DPM suggest increased blood flow to increase oxygen availability. The upregulation of ATP2A1 by DPM induction could be attributable to alterations in calcium ion transportation from the cytoplasm into the sarcoplasmic reticulum.6. The results are evidence of changes in muscle structure and gene expression pathways in p. major muscle of broilers with DPM.
Keywords: Broiler; deep pectoral myopathy; fibre; gene expression; muscle